The Effects of Volatile Salivary Acids and Bases on Exhaled Breath Condensate pH - Effros, Richard M; Casaburi, Richard; Su, Jennifer; Dunning, Marshall; Torday, John; Biller, Julie; Shaker, Reza (American journal of respiratory and critical care medicine, 2006)
Recent studies have reported acidification of exhaled breath condensate (EBC) in inflammatory lung diseases. This phenomenon, designated "acidopnea," has been attributed to airway inflammation. To determine whether salivary acids and bases can influence EBC pH in chronic obstructive pulmonary disease (COPD). Measurements were made of pH, electrolytes, and volatile bases and acids in saliva and EBC equilibrated with air in 10 healthy subjects and 10 patients. The average EBC pH in COPD was reduced (normal, 7.24 +/- 0.24 SEM; range, 6.11-8.34; COPD, 6.67 +/- 0.18; range, 5.74-7.64; p = 0.079). EBCs were well buffered by NH(4)(+)/NH(3) and CO(2)/HCO(3)(-) in all but four patients, who had NH(4)(+) concentrations under 60 micromol/L, and acetate concentrations that approached or exceeded those of NH(4)(+). Saliva contained high concentrations of acetate (approximately 6,000 micromol/L) and NH(4)(+) (approximately 12,000 micromol/L). EBC acetate increased and EBC NH(4)(+) decreased when salivary pH was low, consistent with a salivary source for these volatile constituents. Nonvolatile acids did not play a significant role in determining pH of condensates because of extreme dilution of respiratory droplets by water vapor (approximately 1:12,000). Transfer of both acetic acid and NH(3) from the saliva to the EBC was in the gas phase rather than droplets. EBC acidification in COPD can be affected by the balance of volatile salivary acids and bases, suggesting that EBC pH may not be a reliable marker of airway acidification. Salivary acidification may play an important role in acidopnea.